Diagnosis of SARS-CoV-2 Infection with LamPORE, a High-Throughput Platform Combining Loop-Mediated Isothermal Amplification and Nanopore Sequencing - Leon Peto; Gillian Rodger; Daniel Carter; Karen L. Osman; Mehmet Sunay Yavuz; Katie Johnson; Mohammad Raza; Matthew Parker; Matthew D. Wyles; Monique Andersson; Anita Justice; Alison Vaughan; et al. (2021)
LamPORE is a novel diagnostic platform for the detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA combining loop-mediated isothermal amplification with Nanopore sequencing, which could potentially be used to analyze thousands of samples per day on a single instrument. We evaluated the performance of LamPORE against reverse transcriptase PCR (RT-PCR) using RNA extracted from spiked respiratory samples and stored nose and throat swabs collected at two UK hospitals.